2021
DOI: 10.1111/1468-0009.12518
|View full text |Cite
|
Sign up to set email alerts
|

When All That Glitters Is Gold: Dominated Plan Choice on Covered California for the 2018 Plan Year

Abstract: Purchasing health insurance is a complex task with multiple potential points of failure. In 2018, following the silver‐loading price shock, 20.2% of households earning above 200% of the federal poverty level with coverage through the two Covered California insurers who sold dominated silver plans purchased the inferior, dominated silver plan. Individuals who were automatically reenrolled were more likely to purchase an inferior, dominated plan. Automatic reenrollment rules and marketplace choice architecture s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…This phenomenon, known as dominated health plan choice, is a common occurrence in private health insurance markets, including the health care marketplaces. [4][5][6][7][8] The American Rescue Plan (ARP), signed into law in March 2021, increased premium tax credit subsidies through 2022. These subsidies reduce marketplace plans' premiums for qualifying enrollees.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon, known as dominated health plan choice, is a common occurrence in private health insurance markets, including the health care marketplaces. [4][5][6][7][8] The American Rescue Plan (ARP), signed into law in March 2021, increased premium tax credit subsidies through 2022. These subsidies reduce marketplace plans' premiums for qualifying enrollees.…”
Section: Introductionmentioning
confidence: 99%
“…15 However, this research does not provide detail on enrollee plan selection and cost implications across varying levels of enrollee risk, which limits understanding of the associations between these factors. Furthermore, studies have shown many enrollees make suboptimal selections, despite decision-making nudges, [16][17][18][19] due in part to lack of health insurance literacy and variable assessment of their own health risk. 19 A greater understanding of the distribution of enrollee risk and spending by metal tier may enhance the ability of market administrators, insurance plan designers, and policy makers to offer appropriate insurance products.…”
Section: Introductionmentioning
confidence: 99%
“…Health insurance literacy in the United States is low (Kim et al, 2013). Individuals frequently choose strictly dominated plans where they pay substantially higher premiums for worse coverage relative to other similar options offered by the same insurer (Rasmussen & Anderson, 2021). Inattention and the hassle costs of switching plans are estimated to cost the median household almost $1,800 in foregone consumer surplus (Drake et al, 2022).…”
Section: Introductionmentioning
confidence: 99%